2000
DOI: 10.1002/1099-1026(200007/08)15:4<245::aid-ffj904>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination and characteristic flavour ofCitrus junos (yuzu) peel oil

Abstract: Yuzu (Citrus junos Sieb. ex Tanaka) peel oils were extracted by cold‐pressing. The flavour components of yuzu were quantitatively determined by use of two internal standards with GC and GC–MS. Characteristic flavour components of yuzu were examined by GC–olfactometry. The contents of hydrocarbons (34 compounds), alcohols (37 compounds) and aldehydes (16 compounds) in weight percent were about 96.55%, 2.03% and 0.1%, respectively. The terpenes were the major components of yuzu peel oil, but they contributed lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
2
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 15 publications
6
73
2
3
Order By: Relevance
“…The most common technique used is the gas chromatography coupled to mass spectrometry (GC-MS) for both biological matrices such as plasma and urine, and non-biological matrices such as the volatile fraction of plant extracts. [19][20][21][22][23][24] Methods by liquid chromatography (LC) techniques are also described in the literature, such as liquid chromatography-diode array detection (LC-DAD), [25][26][27][28][29] liquid chromatographyelectrochemical detection (LC-ECD) 30 and liquid chromatography-fluorescence detection (LC-FLD). 31 These papers are devoted to describing chromatographic methods for analytical and bioanalytical quantification of POH, and none of these cases comprise a degradation behavior study.…”
Section: Introductionsupporting
confidence: 92%
“…The most common technique used is the gas chromatography coupled to mass spectrometry (GC-MS) for both biological matrices such as plasma and urine, and non-biological matrices such as the volatile fraction of plant extracts. [19][20][21][22][23][24] Methods by liquid chromatography (LC) techniques are also described in the literature, such as liquid chromatography-diode array detection (LC-DAD), [25][26][27][28][29] liquid chromatographyelectrochemical detection (LC-ECD) 30 and liquid chromatography-fluorescence detection (LC-FLD). 31 These papers are devoted to describing chromatographic methods for analytical and bioanalytical quantification of POH, and none of these cases comprise a degradation behavior study.…”
Section: Introductionsupporting
confidence: 92%
“…α-Copaene and τ-muurolol showed high relative flavor activities ≥ 1 . On the basis of an estimation of the relative flavor activity 10,26,27 , these compounds are regarded as important contributors to the flavor of S. laeteviolacea. These results suggest that minor components often contribute significantly to the characteristic flavor.…”
Section: Aroma Extract Dilution Analysis Aedamentioning
confidence: 94%
“…The aroma compounds of many plants, including Yuzu, are well documented. The Yuzu aroma is mainly determined by a complex mixture of monoterpenes, monoterpene alcohols, and sesquiterpenes [16][17][18][19][20]. We report here our preliminary investigations on the emissions of various aroma compounds from Yuzu.…”
Section: Aroma In the Headspace Of Yuzu Plantsmentioning
confidence: 99%
“…For example, the m/z 143 and 161 peaks, which were assigned to C 10 H 16 Li + and C 10 H 18 OLi + , may consist of assortments of monoterpenes and monoterpene alcohols, respectively. Therefore, the peak assignments in the present study were confirmed by referring to a previous study on volatile products detected by gas chromatographymass spectroscopy in the headspace of Yuzu fruits [16][17][18][19][20].…”
Section: Aroma In the Headspace Of Yuzu Plantsmentioning
confidence: 99%
See 1 more Smart Citation